A Photoactivated Cu–CeO2 Catalyst with Cu‐[O]‐Ce Active Species Designed through MOF Crystal Engineering. Issue 21 (25th February 2020) - Wang, Feifan; Tian, Jie; Li, Mengzhu; Li, Weizhen; Chen, Lifang; Liu, Xiaozhi; Li, Jian; Muhetaer, Aidaer; Li, Qi; Wang, Yuan; Gu, Lin; Ma, Ding; et al.
Abstract: Fully utilizing solar energy for catalysis requires the integration of conversion mechanisms and therefore delicate design of catalyst structures and active species. Herein, a MOF crystal engineering method was developed to controllably synthesize a copper–ceria catalyst with well‐dispersed photoactive Cu‐[O]‐Ce species. Using the preferential oxidation of CO as a model reaction, the catalyst showed remarkably efficient and stable photoactivated catalysis, which found practical application in feed gas treatment for fuel cell gas supply. The coexistence of photochemistry and thermochemistry effects contributes to the high efficiency. Our results demonstrate a catalyst design approach with atomic or molecular precision and a combinatorial photoactivation strategy for solar energy conversion. Abstract : Photoactivated catalysis of the preferential oxidation of carbon monoxide was achieved by using a catalyst with specified and homogeneously dispersed active species. The catalyst was designed through MOF crystal engineering and its integration of photothermal and photoelectric mechanisms realized the full utilization of solar energy with excellent stability.